Furtive Role-Playing and Vulnerability in “Wakefield:” Nathanial Hawthorne and E. L. Doctorow (Global Journal of Human-Social Science, 2019)
In most of his novels Doctorow confirmed that the past is very much alive but that it s not easily accessed writes Jay Parini We tell and retell stories and these stories illuminate our daily lives He showed us again and again that our past is our present 2015 Indeed when Doctorow rewrote Wakefield in 2008 he proposed to fill in gaps unbridged by Hawthorne s Wakefield 1835 Doctorow gives his first-person narrator and protagonist the power to tell the story free from the load of Hawthorne s first person witness narrator who keeps the protagonist under his direct and strict observation Through his protagonist however Doctorow lets us learn the psychological reasons why Wakefield decides to leave his home Besides Doctorow presents the events that happened to Wakefield during his absence in a more probable manner by creating a plot with causative connections between the events In so doing Doctorow seeks to reconnect the past with the present in order to illuminate our present
Keywords: american literature; short fiction; theatrical imagery; vulnerability; narrative point of view and critical theory